A Randomized Comparative Study between High-Intensity and Low-Level Laser Therapy in the Treatment of Chronic Nonspecific Low Back Pain. (29th October 2020) - Abdelbasset, Walid Kamal; Nambi, Gopal; Alsubaie, Saud F.; Abodonya, Ahmed M.; Saleh, Ayman K.; Ataalla, Nahla N.; Ibrahim, Ahmed A.; Tantawy, Sayed A.; Kamel, Dalia M.; Verma, Anju; Moawd, Samah A.
Abstract : Objectives . Chronic nonspecific low back pain (chronic nsLBP) is one of the most common musculoskeletal disorders leading to disabilities and physical inactivity. Laser therapy was used in chronic nsLBP treatment; however, no previous studies have assessed the impacts of high-intensity laser therapy (HILT) versus low-level laser therapy (LLLT) on chronic nsLBP. This study compared the effects of HILT versus LLLT on individuals suffering from chronic nsLBP. Methods . The study was a randomized control trial. Sixty individuals with chronic nsLBP were enrolled in this study between May and November 2019. All participants were clinically diagnosed with chronic nsLBP. They were assigned randomly into three groups, 20 in each group. The first group received a program of LLLT, the second group received a program of HILT, and the third did not receive laser therapy (control group). Pain severity, disability, lumbar mobility, and quality of life were assessed before and after 12-week intervention. Results . Both LLLT and HILT groups showed a significant improvement of the Oswestry Disability Index (ODI), visual analogue scale (VAS), lumbar range of motion (ROM), and European Quality of Life (EuroQol) scores (p > 0.05 ), while the control group did not show significant changes (p > 0.05 ). Comparison among the three study groups postintervention showed significant differences in the outcome measures (p > 0.05 ), while comparison between the LLLT and HILT groups showed nonsignificant differences (p > 0.05 ). Conclusion . There are no different influences of LLLT versus HILT on chronic nsLBP patients. Both LLLT and HILT reduce pain and disability and improve lumbar mobility and quality of life in chronic nsLBP patients.